Prediction of flashover voltage of insulators using least squares support vector machines - Gencoglu, Muhsin Tunay; Uyar, Murat (Pergamon-Elsevier Science Ltd, 2009)
The importance of the research on insulator pollution has been increased considerably with the rise of the voltage of transmission lines. In order to determine the flashover behavior of polluted high voltage insulators and to identify to physical mechanisms that govern this phenomenon, the researchers have been brought to establish a modeling. In this paper, a dynamic model of AC flashover voltages of the polluted insulators is constructed using the least square support vector machine (LS-SVM) regression method. For this purpose, a training set is generated by using a numerical method based on Finite Element Method (FEM) for several of common insulators with different geometries. To improve the resulting model's generalization ability, an efficient optimization algorithm known as the grid search are adopted to tune parameters in LS-SVM design. In addition, two different testing set, which are not introduced to the LS-SVM during the training procedures, is used to evaluate the effectiveness and feasibility of the proposed method. Then, optimum LS-SVM model is firstly obtained and the performance of the proposed system with other intelligence method based on ANN is compared. It can be concluded that the performance of LS-SVM model outperforms those of ANN, for the data set available, which indicates that the LS-SVM model has better generalization ability. (C)2009 Elsevier Ltd. All rights reserved.
Keywords: High voltage insulator; Flashover voltage (FOV); Least square support vector machine (LS-SVM); Grid search